Development of online speed trap system (DOSTS) - Ishak, Maizul (2006)
By generating TTL square wave of the output of a Doppler speed sensor principle and its’ datasheet specification of DRS1000, connected to frequency to voltage converter circuit, PIC 16F877 micro controller with Analog to Digital converter circuit and web camera, a prototype of the Development of Online Speed Trap System (DOSTS) which being created and programmed to detect the signal and calculate the vehicle’s speed. All the data will be sending to GUI (at PC) through serial communication interface (RS232). A development programming of Visual Basic (VB) GUI will gather all the important of information or data as usual as required by the police traffic department for displaying it on the PC monitor. The work in this project is to study, evaluate and compare the output of Doppler principle especially DRS1000`s output, detecting for speed of the vehicles will be the main focus. The study of the output Doppler principle will lead to be used in the VB GUI. As a conclusion, the speed and image of car models using the same of output of DRS 1000, Doppler sensor is verified via programming of VB GUI in term of various speeds